The existence spatial reasoning of preservice teacher in primary mathematics learning - Lingga Nico Pradana (Journal of Educational Studies, 2023)
Spatial reasoning is an ability related to the representation and use of objects and their relationships in the 2D and 3D worlds. This research examines the spatial reasoning’ of pre-service teacher primary education and its use in their course. The subject involved 120 pre-service teachers (60 second years students; 60 third years students; 37 males; 83 females) in the primary education department of Universitas PGRI Madiun. The measurement uses a spatial reasoning test based on three constructs: spatial visualization, mental rotation, and spatial orientation (20 items spatial visualization; 20 items spatial orientation; 20 items mental rotation). The test was used to choose subjects with high spatial ability in every three aspects. Then, the selected subject was observed to view the use of spatial reasoning ability. This research results in spatial reasoning ability used to explain objects, draw objects, and the relations between objects in the classroom. That is the possible way to improve student achievement through spatial reasoning ability used by teachers.